2023
DOI: 10.1172/jci.insight.161042
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and single-cell RNA-Seq survey of the Helicobacter pylori–infected stomach in asymptomatic individuals

Abstract: Helicobacter pylori colonization of the gastric niche can persist for years in asymptomatic individuals. To deeply characterize the host–microbiota environment in H . pylori –infected (HPI) stomachs, we collected human gastric tissues and performed metagenomic sequencing, single-cell RNA-Seq (scRNA-Seq), flow cytometry, and fluorescent microscopy. HPI asymptomatic individuals had dramatic changes in the composition of gastric microbiome and immune cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 88 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…Innate immune cells, particularly monocytes, are known to rapidly extravasate from blood vessel to sites of ongoing inflammation and infection ( 31 , 32 ). Accordingly, monocytes can be found in increased numbers in H. pylori -infected murine ( 33 ) and human epithelial tissue ( 3 ). Activation of monocytes and other myeloid cells can be further regulated by functional adaptations induced by previous encounters with various priming agents, and these adaptations can lead to both a reduction as well as an increase in inflammatory potential of an immune cell – referred to as tolerance and training, respectively ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Innate immune cells, particularly monocytes, are known to rapidly extravasate from blood vessel to sites of ongoing inflammation and infection ( 31 , 32 ). Accordingly, monocytes can be found in increased numbers in H. pylori -infected murine ( 33 ) and human epithelial tissue ( 3 ). Activation of monocytes and other myeloid cells can be further regulated by functional adaptations induced by previous encounters with various priming agents, and these adaptations can lead to both a reduction as well as an increase in inflammatory potential of an immune cell – referred to as tolerance and training, respectively ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This hyperactivity could contribute to gastric pathology and inflammation in the context of H. pylori infection. The spike in innate immune cell reactivity after contact with the pathogen could also concurrently contribute to the disappearance of other bacterial species from the gastric compartment in presence of the H. pylori : several reports have shown dramatic gastric microbiota composition changes upon infection with H. pylori , as the microbial diversity of the stomach severely decreases in H. pylori -positive individuals ( 3 , 51 , 52 ). Intriguingly, Ferreira and colleagues reported that dysbiosis and loss of microbial richness was even more pronounced in gastric carcinoma samples ( 53 ), albeit the relative abundance of H. pylori decreased, implying that the damage may have been done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 In addition, metagenomic and single-cell RNA-Seq analysis revealed dramatic changes in the composition of gastric microbiome and immune cells in Hp -infected asymptomatic individuals. 23 Eradication of Hp also induced increased long-term resistant bacteria communities in the gut. 24 These imply an interplay between Hp and gastrointestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori (Hp) is the etiologic agent most closely associated with intestinal-type GC, 19,20 and most prior studies of gastric precursors have either focused on Hp-infected individuals or have drawn from populations with high Hp prevalence. [21][22][23][24] However, Hp infection has been rapidly declining in Western nations, and most patients diagnosed with GIM have undergo bacterial eradication per clinical guidelines. 25 Moreover, patients with GIM remain at significantly elevated risk even following Hp eradication.…”
Section: Introductionmentioning
confidence: 99%